OC-018 Validation of two APC-dependent potential biomarkers of colorectal carcinogenesis. (28th May 2012) - Ibrahim, S A; Reed, K R; Song, F; Hammoudi, A; Pritchard, D M; Jenkins, J R
Abstract : Introduction: Most cases of sporadic colorectal cancer develop via the adenoma carcinoma sequence and APC mutation is a key early molecular event. APC regulates B-catenin function and the WNT signalling pathway to control intestinal homeostasis. However, mutation or loss of APC gene results in translocation of B-catenin into the nucleus, where it forms a heterodimeric transcriptional factor complex with TCF and results in altered cell fate. We have previously performed a proteomic analysis of changes which occur in murine intestinal epithelium following acute b-napthoflavone-induced deletion of Apc expression (Apc fl/fl mice). Several proteins showed increased abundance following intestinal Apc deletion and we hypothesised that some of these may represent potential biomarkers for the serological detection of the early stages of human colorectal cancer. Aims: To investigate whether two proteins which were demonstrated to be upregulated in Apc fl/fl intestinal epithelium by proteomic analysis, namely serine/arginine-rich splicing factor 2 (SRSF2) and ribosomal protein L6 (RPL6) show altered expression in murine and human intestinal tumours. Methods: The expression patterns of SRSF2 and RPL6 were assessed by immunohistochemistry and RTqPCR in intestinal and colonic tumour samples obtained from Apc Min/+ mice aged 1, 3 and 6 months and 15 human subjects with colorectal cancer. Results: RTqPCR demonstrated a 3.0-fold increase in SFRS2 expression and a 2.8-fold increase in RPL6 expression in colonic polyp tissue from 6-month old Apc Min/+ mice relative to colonic tissue from Apc +/+ wild-type mice of the same age. Immunohistochemistry showed nuclear rather than cytoplasmic localisation of both SFRS2 and RPL6 in intestinal and colonic polyps from Apc Min/+ mice aged 3 months and 6 months. The alteration in subcellular localisation of SFRS2 and RPL6 appeared to occur in adenomatous cells which also displayed nuclear translocation of B-catenin. Statistically significant increases in the relative expressions of SFRS2 (1.2-fold) and RPL6 (1.9-fold) mRNAs were also observed in human colorectal cancer tissue samples relative to adjacent unaffected colonic tissue from the same patients. Conclusion: RPL6 and SFRS2 both showed altered expression in murine and human intestinal/colonic tumours. Both these proteins are involved in regulating cell cycle progression—RPL6 regulates the G1-S transition via cyclin E and SFRS2 affects the G2/M transition via CDC5, possibly through alternative splicing. The altered expressions of PRL6 and SFRS2 may therefore deregulate cell cycle control and promote cellular proliferation, a characteristic phenotype of the intestinal epithelium of Apc fl/fl mice as well as intestinal tumours. Competing interests: None declared.